Geoelectric analysis for groundwater potential assessment and aquifer protection in a part of Shango, North-Central Nigeria - J. S. Ejepu; M. O. Jimoh; S. Abdullahi; I. A. Abdulfatai; S. T. Musa; N. J. George (Discover Water, 2024)
Abstract Groundwater is vital for sustainable development, and this study addresses potable water challenges in Shango, North-Central Nigeria. The main goal is to identify optimal sites for new wells and boreholes, utilizing geological and geo-electrical attributes from existing boreholes and wells. Vertical Electrical Sounding (VES) assessed groundwater potential, aquifer protection, and overburden corrosivity. Sixteen VES stations were probed using Schlumberger array with a maximum current electrode spacing (AB/2) of 200 m using a resistivity meter. The data were interpreted using an automatic computer inversion program, IPI2WIN. The VES results revealed five subsurface geo-electric units, with depths to the aquifer ranging from 58 to 68 m, each exhibiting distinct characteristics contributing to the lithological variability of the research area. Hydraulic conductivity ranged from 0.465 to 0.534 m/day, while transmissivity varied from 9.589 m2/day to 26.029 m2/day across different VES points. Regions exhibiting thick layers and low resistivity values indicate high longitudinal conductivity. Furthermore, areas with low protective capacity are susceptible to the risks of pollution and contamination stemming from leaks and waste sites. The study revealed that all VES points are in practically non-corrosive zones, making them suitable for burying underground tanks with extremely low deterioration rates. Based on geoelectrical characteristics, the study area was divided into three groundwater potential zones: low, medium, and high. These findings provide valuable insights into the groundwater potential and protective capacity of the Shango area, while emphasizing on the vulnerability of these regions and highlighting the pressing need for appropriate preventive measures to safeguard against potential environmental hazards.